Modeling the Continuance Intention to Use Automated Writing Evaluation Among Chinese EFL Learners - Li, Rui (SAGE open, 2021)
Despite the growing attention being paid to the use of Automated Writing Evaluation (AWE) in China, it is still uncertain what factors lie behind EFL (English-as-a-foreign-language) learners’ continuance intention to use it. To this end, by adding two external factors (i.e., computer self-efficacy and perceived ease of use) to the expectation confirmation model (ECM), we surveyed 345 Chinese EFL learners and tested a number of proposed hypotheses using their response data. Data were analyzed using descriptive statistics and structural equation modeling (SEM). Results demonstrated that four factors directly influenced EFL learners’ continuance intention to use AWE, of which perceived ease of use was the most significant factor. Furthermore, confirmation was the most important factor impacting on EFL learners’ satisfaction and perceived ease of use of AWE. Perceived ease of use of AWE played an important role in influencing EFL learners’ perceived usefulness of AWE. Implications regarding the findings were also discussed.